EVALUASI PROGRAM KESETARAAN PAKET C BERBASIS MODEL PROVUS DI PKBM BUDI UTAMA - Loekman, Asma Syafiqo; Wandasari, Hestia; Pratiwi, Arsyrahma Eka; Kusuma, Nur Indah Lestari (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
The evaluation of the Package C equality program based on the provus model at PKBM Budi Utama is in accordance with what happened in the Package C equality education program where there were several gaps, namely in terms of accreditation, graduation, and learning skills. The aim of the Provus Evaluation Model at the PKBM Budi Utama educational institution is to determine whether to replace or revise, continue, modify or stop a program. This research uses a qualitative descriptive method, with research data sources using purposive sampling techniques. Data collection was carried out by interviews, observation and documentation, data analysis techniques used in this research were reducing data, displaying data, and verifying data. With this provus evaluation, it is hoped that we will be able to determine the level of conformity between the standards that have been determined in the program and the actual performance of the program. Therefore, the standards in a criterion can be measured through the stages that are realized, namely: design preparation stage, installation stage, process stage, objective measurement stage, and comparison stage. Evaluation of the provus model for the Package C equality education program at PKBM Budi Utama has been realized according to the stage level, and there are actions in the form of continuation or improvement by carrying out several improvement notes to improve the results that have been achieved previously.